Perilaku Kepatuhan Wajib Pajak Badan - HARINURDIN, ERWIN (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
This research was carried out to research the behavior of the company’s tax compliance especially the big company that was registered in the Large Tax Ofce in Jakarta. The design of this research was the survey research by using the instrument of the questionnaire. The data in the analysis by using Structural Equation Modeling (SEM) with the LISREL program 8,54. This research found proof that was the same as the research beforehand Bradley (1994), Bobek (2003), Lussier (200), Sihaan (2005) and Mustikasari (2007) those are (1) the Perception of the control behavior have positive and signicant the professional intention to the tax compliance. (2) the professional intention have inuential tax positive and signicant of the company’s tax compliance, (3) the Perception of the condition for the company’s have positive and signicant of the company’s tax compliance, (4) the Perception of the company’s facilities have positive and signicant the company’s tax compliance, (5) the Perception of the Climate Organization have positive and signicant of the company’s tax compliance. Whereas the variable (6) the perception of the control behavior have not signicant was directly of the company’s tax complian